Pemodelan Dan Simulasi Kinerja Downdraft Gasifier Menggunakan Teknik Minimisasi Energi Bebas Gibbs - Rio Nanda Novendra; Zuchra Helwani; Sri Helianty; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Gibbs free energy minimization method has been used in modelling the performance of a downdraft gasifier. The performance is represented by the composition of resulting gas. Sixteen gases considered are H2, CO, CH4, H2O, CO2, N2, C2H2, C2H4, C2H6, NO, NO2, N2O, HCN, NH3, H2S and SO2. The simulation is carried out making used of EXCEL. The result showed that the predicted value of model fit reasonably well with experimental data. The model was also used to investigate the influence of biomass composition, oxidant ratio and composition of oxidizing agent to composition of the resulting gas. Three kinds of biomass considered are oil palm shell,oil palm frond and empty fruit bunch. The oxidant ratio simulated is varied from 0 to 1 while composition of oxidizing agent is varied from 21% - 100% oxigen. The simulation result showed that those three parameters play an important role in gasification process which in combination can produce total H2 and CO up to more than 85%.Keyword : Gasification, modelling, downdraft gasifier, Gibbs free energy minimization